Voxelotor Treatment Interferes With Quantitative and Qualitative Hemoglobin Variant Analysis in Multiple Sickle Cell Disease Genotypes. Issue 5 (20th June 2020) - Rutherford-Parker, Nicola J; Campbell, Sean T; Colby, Jennifer M; Shajani-Yi, Zahra
Abstract: Objectives: Voxelotor was recently approved for use in the United States as a treatment for sickle cell disease (SCD) and has been shown to interfere with the quantitation of hemoglobin (Hb) S percentage. This study aimed to determine the effect of voxelotor on the quantitation of hemoglobin variant levels in patients with multiple SCD genotypes. Methods: In vitro experiments were performed to assess the impact of voxelotor treatment on hemoglobin variant testing. Whole blood samples were incubated with voxelotor and then analyzed by routinely used quantitative and qualitative clinical laboratory methods (high-performance liquid chromatography [HPLC], capillary zone electrophoresis [CZE], and acid and alkaline electrophoresis). Results: Voxelotor modified the α-globin chain of multiple hemoglobins, including HbA, HbS, HbC, HbD-Punjab, HbE, HbA2, and HbF. These voxelotor-hemoglobin complexes prevented accurate quantitation of multiple hemoglobin species, including HbS, by HPLC and CZE. Conclusions: Technical limitations in quantifying HbS percentage may preclude the use of HPLC or CZE for monitoring patients treated with voxelotor. Furthermore, it is unclear whether HbS-voxelotor complexes are clinically equivalent to HbS. Consensus guidelines for reporting hemoglobin variant percentages for patients taking voxelotor are needed, as these values are necessary for determining the number of RBC units to exchange in acute situations.